2013
DOI: 10.1016/j.healthplace.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

The problems of a ‘dirty workplace’ in domiciliary care

Abstract: Abstract'Dirty work' is an acknowledged part of domiciliary care, with tasks such as bathing and toileting, but there is little examination into whether the workplaces may also be dirty. Domiciliaries' workplace is the client's own home, but this space has been under-researched and is often not considered essential to client's care in policy. Through shadowing and interviews with domiciliaries, managers and stakeholders this paper suggests that in the most extreme cases the workplace may be dirty. Arguably 'di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Due to this variability, it is reasonable to explore whether HC staff exposures to occupational safety hazards differ by geographical setting. In the HC literature, some studies provide descriptive reports of the geographical settings of their samples for context and generalisability of study findings (Haiduven & Ferrol 2004, Henriksen et al 2008, Sherman et al 2008, Wibberley 2013, Quinn et al 2015; however, few incorporate rural and urban contexts into their analysis (Meyer & Muntaner 1999, Sitzman et al 2002, Gershon et al 2008a. In this paper, HC occupational safety hazards will be described with the focus on examining differences among four geographical settings along the rural-to-urban gradient.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this variability, it is reasonable to explore whether HC staff exposures to occupational safety hazards differ by geographical setting. In the HC literature, some studies provide descriptive reports of the geographical settings of their samples for context and generalisability of study findings (Haiduven & Ferrol 2004, Henriksen et al 2008, Sherman et al 2008, Wibberley 2013, Quinn et al 2015; however, few incorporate rural and urban contexts into their analysis (Meyer & Muntaner 1999, Sitzman et al 2002, Gershon et al 2008a. In this paper, HC occupational safety hazards will be described with the focus on examining differences among four geographical settings along the rural-to-urban gradient.…”
Section: Introductionmentioning
confidence: 99%
“…HC workers are often exposed to bodily fluids (Quinn et al . , , Wibberley , Markkanen et al . ), increasing the risk of communicable disease transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these aspects were already identified by previous studies on the care relationship in the context of home care, such as dirtiness/cleanliness of the care setting and the care-receiver's body ( e.g. Twigg, 2000; Isaksen, 2002; Wibberley, 2013), respect and trust (Trojan and Yonge, 1993; Tadd and Calnan, 2009), ignoring/not ignoring ( e.g. Tadd and Calnan, 2009), privacy ( e.g.…”
Section: Discussionmentioning
confidence: 94%
“…The presence of odours, sights and textures produce a feeling of disgust in care providers and a disruptive effect on close relationships (Isaksen, 2002). It is suggested that in the most extreme cases the care-receiver's home may also be dirty, and a ‘dirty workplace’ may have negative impacts upon care workers ‘through unofficially increasing their workload, further devaluing their work and risking their wellbeing’ (Wibberley, 2013: 156). Second, body work is dirty work because it is pushed to private realms by a society that puts a high public value on youth and success and has an aversion to decay, failure and death.…”
Section: Theorising the Fourth Age And Carementioning
confidence: 99%